PERAN PENDIDIKAN DALAM PENYULUHAN AGAMA DI MASYARAKAT - Munawiroh Munawiroh (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2014)
This paper draws on the results of research on the Role of Education in Religious Counseling in the Community, which describes how education plays its role in religious counseling activities. The study was conducted in seven provinces, i.e. East Java, West Java, Central Java, North Sumatra, Bali, Central Kalimantan and East Nusa Tenggara. The data were collected by using questionnaires. The fi ndings show that religious counselors understand about the education role they must play in their counseling programs. The activities categorized as the role of education in counseling include religious sermons, regular recitation, group discussion, and individual consultations. The materials provided may vary according to the needs of the community. On the other hand, the obstacles during the performance of their education role include, among others, considered low benefi ts, inadequate means of transportation, short availability of textbooks, and lack of public enthusiasm in participating in the counseling.